2007
DOI: 10.1167/iovs.07-0433
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Apparent Ion Demand in Experimental Diabetic Retinopathy: Correction by Lipoic Acid

Abstract: The present results support the hypothesis that LPA can correct the impaired apparent ion demand in experimental diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 37 publications
6
68
3
Order By: Relevance
“…In any event, based on the literature it was unclear if retinaldehydes would have antioxidant properties in the present context of the retina and diabetes. 4,5,29,74 Our data present undisputable evidence that retinoids administered systemically lower the level of retinal oxidative stress and correct three assays of rod function (transretinal recordings, MEMRI, and ADC), an unlikely scenario if all-trans is toxic in our diabetic model. 6 These results may seem surprising given other evidence that strong light in non-diabetic models increased levels of alltrans-retinaldehyde, which presumably activated NADPH oxidase, thus killing the photoreceptor.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In any event, based on the literature it was unclear if retinaldehydes would have antioxidant properties in the present context of the retina and diabetes. 4,5,29,74 Our data present undisputable evidence that retinoids administered systemically lower the level of retinal oxidative stress and correct three assays of rod function (transretinal recordings, MEMRI, and ADC), an unlikely scenario if all-trans is toxic in our diabetic model. 6 These results may seem surprising given other evidence that strong light in non-diabetic models increased levels of alltrans-retinaldehyde, which presumably activated NADPH oxidase, thus killing the photoreceptor.…”
Section: Discussionmentioning
confidence: 51%
“…1,[3][4][5][6] Although the nature of the rod dysfunction is not entirely understood, it likely involves dysregulation of photoreceptor ion channels. 5,[7][8][9][10][11] For example, rod cell calcium channels, which are normally open in the dark, are paradoxically closed in dark adapted diabetic mice as measured by manganeseenhanced MRI (MEMRI), the imaging modality of choice for studying retinal L-type calcium channel regulation in vivo. 3,[12][13][14][15][16][17][18][19][20][21][22] In an initial study, diabetic mice treated with a single intraperitoneal (i.p.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting its safety, the vector did not modify the retinal vascular bed and the ERG in non-diabetic rats. Finally, we explored the thinning of the retina which, owing to the neurodegeneration of the inner retina, occurs in diabetic humans, [42][43][44][45] and in some, [46][47][48][49] but not all, 50 diabetic rodent studies. We confirmed that retinal thinning does not occur at 6 weeks post-STZ-treatment, 47,49 and showed that the AAV2 vasoinhibin vector did not modify it.…”
Section: Aav2 Vectors Reverse Diabetic Retinal Alterations N Díaz-lezmentioning
confidence: 99%
“…It was reported that the levels of H 2 0 2 , which is a specific quantitative biochemical marker for oxidative stress, is increased with the functional severity of hyperglycemia in the retina of diabetic animals. However, supplement of antioxidant agents such as Aminoguanidine and alpha-lipoic acid was shown to improve retinal function in diabetic animals [42,43]. MMP-2 and -9, induced in response to hyperglycemia are associated with increased ROS (such as hydroxyl radicals and superoxide) production and decreased ROS scavengers (i.e., antioxidants) in the retina-derived endothelial cells in diabetes [26,37].…”
Section: Mmps and Oxidative Stressmentioning
confidence: 99%